(untitled) (Revista Contexto & Saúde, 2023)
The objective of the research was to evaluate the effect of adding beet flour (BF) in cookie on sensory acceptability of children. Also, determine the physical-chemical composition of the standard formulation and the one containing the highest BF content and with acceptance similar to the standard. For the study, five cookie formulations were created with different levels of BF: F1 (0%), F2 (3.5%), F3 (7%), F4 (10.5%) and F5 (14%). Seventy-nine children aged between 7 and 10 years old participated in the research. The addition of levels greater than 7% of BF reduced the sensory acceptability (p<0.05) of the cookie for all attributes and for global acceptance and purchase intent, in relation to the standard product. Formulation F3 was the one with the highest BF content and with acceptance similar to the standard, thus being chosen for comparison. Higher moisture, ash, protein and dietary fiber contents were observed for F3, while carbohydrate and calorie contents were more expressive in F1 (p<0.05). There was no significant difference (p>0.05) between the lipid contents of the products. It is concluded that a level of addition of up to 7% of BF in cookie is well accepted by children, obtaining sensory acceptance similar to the standard product. In addition, it improves the nutritional profile of the food, increasing the levels of minerals, protein and dietary fiber. In this way, BF can be considered a potential ingredient for addition to cookie and similar products, and can be offered to children.